Cold bonding of alumina: Fractured and re-bonding under compression. Issue 1 (January 2020) - Liu, Fangming; Ding, Wei; Liu, Jin; He, Duanwei
Abstract: Cold bonding of metals necessitates high normal/frictional loads, or ultrahigh-vacuum treated atomically flat ductile surface. In case of ceramics composed of ionic and/or covalent bonds, the high diffusion barrier of ions or atoms gives them a constraint to bond together at room temperature. However, from this investigation, it has been found that alumina crystals could be well bonded at room temperature under high pressure. Also, it has been noticed that if the pressure is capable of yielding and breaking down alumina crystals, it could then re-bond the fractured crystals by reducing the distance of their surface atoms to meet the condition for bonding. Overall, we demonstrate a process for the cold bonding of alumina under high pressure with grain fracturing and re-bonding.